Enjoyment takes time: Some implications for choice theory - Sergio Nisticò (Kiel Institute for the World Economy (IfW), 2014)
The paper suggests that casting the choice problem in terms of alternative time-consuming activities can foster the fruitful cross-fertilization between economics and psychology along the lines suggested by Scitovsky in the Joyless Economy. The first part emphasizes how mainstream, utility-based choice theory has eradicated "time" from the analysis, in contrast with the seminal contribution to the subjective theory of value proposed by Gossen in 1858. The limits of Becker's well-known approach to time-use are also analyzed. The second part opens with the presentation of an alternative approach based on activities, intended as productive processes allowing for pleasant time to be produced by consuming "direct" unpleasant time plus the "indirect" amount of unpleasant time equivalent to the market goods used up as inputs. Finally, the approach is applied to an intertemporal context by drawing on Hicks's temporary equilibrium method. Scitovsky's distinction between defensive and creative activities is discussed in conclusion, suggesting that individuals might refrain from engaging in more skilled, time-consuming activities because of the attractiveness of a certain, higher present-period rate of return of less skilled, goods-intensive activities.
Keywords: B41; D03; D11; D81; 330; Time use; consumption Activities; behavior; choice